The Influence of Using the Learning Management System Pacak Spensa and ICT Skills on Student’s Learning Motivation - Turnip, Ramson; Arafat, Yasir; Putra, Muhammad Juliansyah (Yayasan Sembilan Pemuda Indonesia, 2024)
This research aimed to determine the influence of the Spensa Pacak Learning Management System application and the ICT skills of subject teachers on students’ learning motivation. The study was conducted at SMP Negeri 1 Koba, Central Bangka Regency, using questionnaires. The results showed that the use of the Learning Management System application had no significant impact on students’ learning motivation. However, the ICT skills of subject teachers had a significant influence on students’ motivation. The use of the Learning Management System application and subject teachers’ ICT skills simultaneously had a significant influence on students’ motivation. The coefficient of determination for students showed a large influence of the Learning Management System application and subject teachers’ ICT skills, with 82.3% influenced by other factors not mentioned in the research.